Late-season nitrogen applications in high-latitude strawberry nurseries improve transplant production pattern in warm regions - Kirschbaum, Daniel Santiago (2010)
The influence of late-season nitrogen (N) applications on the fruiting pattern of strawberry runner plants of ‘Camarosa’ was determined over three growing seasons. Experiments were carried out in high-latitude nurseries in northern California and fruit production trials were established in southern California. A total of 80 kg/ha of foliar nitrogen was delivered in three applications to the nursery in late summer. Late-season foliar nitrogen applications: (1) increased early yields (+22% on average) as well as the number of early marketable fruit, (2) did not affect total season yields, fruit size, appearance and firmness and (3) resulted in greater N concentration in leaves, crowns and roots. Runner plants with leaf N concentration within the sufficiency range (1.9 - 2.8% of dry mass) produced the highest early yields. Total nonstructural carbohydrate concentrations decreased in most of the N-treated plants. Apparently, nursery late-season foliar nitrogen applications enhance N mobilization to crown and root, stimulate plant activity during the period of flower differentiation after planting, accelerating flower development and contributing to the advancement of fruit production.